Inferior Vena Cava Collapsibility Index Assessed by 3D Echocardiography: A Novel Tool for the Assessment of Right Atrial Pressure in Heart Failure Patients - Wetterling, Friedrich (My University, 2019)
Background: Inferior vena cava (IVC) size and respirophasic collapsibility by 2D transthoracic echocardiography (2DE) have previously been shown to correlate weakly with right atrial pressure (RAP) in patients with acute decompensated heart failure (ADHF). Accurate 2DE dimensions are reliant on obtaining the correct imaging plane and the assumption that the mostly elliptical IVC shape is circular, a limitation that 3D echocardiography (3DE) can overcome. The aim of study was to determine the relationship between invasively obtained RAP and IVC collapsibility as determined by 3DE in patients with ADHF. Methods: Simultaneous measurements of RAP and 3DE recordings of the IVC were performed in ADHF patients during clinically indicated right heart catheterizations. Cross-sectional area and major and minor axis dimensions (Tomtec) were obtained at rest and end inspiration. An IVC collapsibility index was calculated for cross-sectional area (3DE) using the following equation: ((Maximum area- Minimum area)/ Maximum area) * 100. Results: 20 patients were enrolled. Mean age was 59 + 16 years, 52% were male, and 60% of the patients were African American. 80% of the patients were NYHA class III or IV, mean creatinine was 1.9 + 1.4 mg/dl, mean NT-proBNP was 6729 + 6142 pg/mL and mean left ventricular ejection fraction was 31 +17%.Mean RA pressure was 12.7 +6.5 mm of Hg . RAP and IVC volume did not correlate well (r=0.17), regardless of whether RAP was low or high. There was a strong correlation between RAP and IVC collapsibility index (r= 0.63) ( Figure 1). Conclusion: 3DE derived IVC collapsibility index is a novel noninvasive tool to assess RAP.RAP does not appear to correlate to IVC size or volume as measured by 3DE in patients with ADHF. Further studies are needed to characterize this parameter’s role in patient management.
Journal of the American Society of Echocardiography
PUBLISHED